Eksistensi Drama Tari Gambuh di Desa Adat Pedungan, Kelurahan Pedungan, Kecamatan Denpasar Selatan - Ade Mahendra, Rizky; Suwena, I Wayan; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 4 No 2 (2020)DO - 10.24843/SP.2020.v4.i02.p03, 2021)
The dance drama gambuh is a performing art in the form of total theater. In addition to the dominant elements of dance, there are also elements of other arts such as percussion, literary arts, vocal / dialogue arts, fine arts, and make-up that are harmoniously integrated and beautiful. The dance drama gambuh has become a sacred dance in Pedungan Traditional Village, Pedungan Village. Currently the development of the dance drama gambuh is no longer a foreign art among teenagers, this is evidenced by the high interest of teenagers who want to dance this dance when it is performed at temples and at Balinese art parties. Thedance drama gambuh has succeeded in introducing its dance outside the province and even abroad to be precise in Germany. Thus this research formulates the following problems, (1) the existence of the dance drama gambuh in Pedungan Traditional Village, Pedungan Village and (2) the meaning of the dance drama performance gambuh in Pedungan Traditional Village, Pedungan Village. This research uses the structural functional theory from Radcliffe-Brown, the symbolic interpretive theory from Clifford Geertz, and the theory of the meaning of symbols proposed by Victor Turner. These three theories are used because they have a relationship in the dance drama gambuh. The data collection technique starts with the informant determination technique, the observation technique, and the interview technique. This dance drama performance gambuh has meanings contained in the story such as religious meaning, aesthetic meaning, socio-cultural meaning, education meaning, and identity meaning. The results of this study reveal that the dance drama gambuh still exists among children, adolescents, and adults. With the establishment of the Kerta Jaya studio, which was built by I Kadek Sudiarta dance drama gambuh this can be introduced to children as the next generation so that dance drama gambuh this doesn’t disappear. The dance drama gambuh has also become an identity in Pedungan Village.